Legal Protection For Victims Of Misuse Of Personal Data When Making Online Loans - Arabin Sandika; Cholidi Zainuddin; Arief Wisnu Wardhana (Jurnal Ilmiah Advokasi, 2024)
Current developments are investments that take advantage of the digital era and globalization using application products, namely financial technology (Omarova, 2020). Financial technology is a combination of financial services and technology that makes changes to businesses that were previously conventional to become modern. Then, with modern technology, things are illegal and use other people's data. This research method uses normative juridical or doctrinal juridical research. The formulation of the problem is legal protection for victims of misuse of personal data when making online loans. The result is that legal protection can take the form of civil legal protection, criminal legal protection. Including those contained in the Financial Services Authority (OJK) regulations, however, this legal instrument does not yet comprehensively regulate the misuse of personal data for online loans.. Keywords: personal data; victim; legal protection; abuse; online loans.